Jurnalisme Warga Mencegah Hoax melalui Turnbackhoaxid - Aditya Alif Saputro (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Indonesia is one of the countries with a high rate of hoax news dissemination in the world, particularly through social media, which has a wide reach and high speed of information distribution. This phenomenon poses serious challenges to information literacy and the quality of democracy, requiring collective efforts to address it. One emerging initiative is citizen journalism conducted through the Instagram account TurnBackHoax.id, managed by the Indonesian Anti-Slander Society (MAFINDO). This study aims to identify the elements of citizen journalism developed by this account in preventing the spread of hoax news. The research method used is descriptive qualitative, with the primary data source being posts on the TurnBackHoax.id Instagram account. Data were analyzed to uncover the roles, processes, and strategies used by the account managers. The results show that the account managers are ordinary citizens who are members of MAFINDO, not professional journalists, but have received training in identifying and verifying suspected hoax information. They utilize reports from the public, source tracing, and digital verification techniques to determine the authenticity of news. The TurnBackHoax.id account actively publishes its findings on social media, complete with explanations and evidence to confirm whether information is factual or hoax. Research findings indicate that identified hoaxes cover a wide range of areas, including social, cultural, political, and economic issues. This activity reflects the practice of citizen journalism, which positions the public as active subjects in the production and distribution of accurate information. In conclusion, TurnBackHoax.id plays a significant role in building a healthy information ecosystem in Indonesia. This initiative demonstrates that active citizen participation in journalism can be an effective strategy to reduce the spread of hoaxes, improve digital literacy, and strengthen community resilience to disinformation.